Human recognition in unconstrained environments : using computer vision, pattern recognition and machine learning methods for biometrics - De Marsico, Maria; Nappi, Michele; Proenca, Hugo (Academic Press, an imprint of Elsevier, 2017)
Providing a unique picture of the complete in-the-wild biometric recognition processing chain, this book covers everything from data acquisition through to detection, segmentation, encoding, and matching reactions against security incidents. --